Autonomous Aldosterone Secretion as a Subclinical Form of Primary Aldosteronism: Pathogenesis and Clinical Significance - Kmieć, Piotr; Sworczak, Krzysztof (Experimental and Clinical Endocrinology & Diabetes, 2021)
In recent years, a substantial prevalence of primary aldosteronism (PA) has been demonstrated in both normotensive and mildly hypertensive cohorts. Consequently, a classic presentation of the syndrome, i. e. moderate-to-severe and resistant hypertension with concomitant hypokalemia, should be considered a tip-of-the-iceberg phenotype of a wide PA spectrum. Its entire range encompasses the non-classic clinical forms of mild hypertension and prehypertension but also several biochemical presentations, including patients who meet PA screening and confirmation test criteria, as well as those with either of them and those with other parameters indicating mineralocorticoid excess. In the current review, research insights on the pathogenetic background and clinical significance of autonomous aldosterone secretion (AAS) are presented, which is defined as a constellation of either: 1) normotension, normokalemia, a positive PA screening (high aldosterone-to-renin ratio) and/or confirmation test, or 2) hypertension, normokalemia and a positive PA screening but negative confirmation test. For this purpose, a literature search of the PubMed database was conducted. Advances in immunohistochemistry and genetic sequencing of isolated adrenal cells are provided as probable morphologic basis of the wide range of aldosterone secretion autonomy. Also, the role of corticotropin as an aldosterone secretagogue is discussed. To date, clinical studies depict consequences of subclinical PA phenotypes, such as increased mortality and risk of developing hypertension, impaired arterial and kidney function, association with metabolic syndrome and age, as well as osteoporosis.
Keywords: hyperaldosteronism etiology; aldosterone; renin; hypertension; adrenal glands physiopathology; hyperaldosteronism diagnosis